2020
DOI: 10.21203/rs.3.rs-70145/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic Models for Knee Osteoarthritis: A Protocol for Systematic Review, Critical Appraisal and Meta-Analysis

Abstract: Background: Osteoarthritis is the most common degenerative joint disease diagnosed in clinical practice. It is associated with significant socioeconomic burden and poor quality of life, a large proportion of which is due to knee osteoarthritis (KOA), mainly driven by total knee arthroplasty (TKA). As the difficulty of being detected early and deficiency of disease-modifying drug, the focus of KOA is shifting to disease prevention and the treatment to delay its rapid progression. Thus, the prognostic prediction… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(76 reference statements)
0
2
0
1
Order By: Relevance
“…We are unaware of any other previously published review of multivariable risk prediction models for OA incidence with which to compare our findings, although we note a published protocol of a review in development relating to prognostic models for knee OA (56). Reviews in other fields have found similar concerns over methodologic quality and applicability of multivariable prediction models for disease incidence (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 94%
“…We are unaware of any other previously published review of multivariable risk prediction models for OA incidence with which to compare our findings, although we note a published protocol of a review in development relating to prognostic models for knee OA (56). Reviews in other fields have found similar concerns over methodologic quality and applicability of multivariable prediction models for disease incidence (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 94%
“…Además, las anomalías en la alineación de la rodilla, el empuje del varo al caminar y el aumento del momento de aducción y flexión de la rodilla son factores de riesgo para la progresión de la artrosis de rodilla, lo que pone de relieve la importancia de comprender estos factores para prevenir la enfermedad [17]. Faltan métodos de detección temprana y fármacos modificadores de la enfermedad, lo que subraya la necesidad de contar con modelos de predicción pronóstica que guíen la toma de decisiones clínicas en el tratamiento de la artrosis [18].…”
Section: Pronósticounclassified

Actualización en Traumatología Vol. 9

Quinchi Maicelo,
Crespo Cordero,
Maldonado García
et al. 2024
“…Data will be synthesized by a meta-analysis if the number (at least 5) of studies included is large enough in a subset with an analogous clinical question appraised repeatedly [33]. A meta-analysis of validation studies for a common prediction model will also be performed if feasible.…”
Section: Quantitative Synthesesmentioning
confidence: 99%